Penguatan Kapasitas Orang Tua dalam Pendampingan Psikologis Korban Bullying di Madrasah Diniyah Miftahul Ulum Kesugihan Pulung Ponorogo - Siti Kalimah; Diyan Putri Ayu (Social Science Academic, 2023)
Bullyingis a phenomenon that is familiar in Indonesia and abroad. In developing the role of advocacy for victims of bullying, there needs to be cooperation from both parents and teachers at school / madrasah. The service was carried out in the village of Kesugihan, Pulung District, Ponorogo Regency. Service activities are carried out on a research basis which aims to strengthen the capacity of parents in psychological assistance to victims of Bullying (children) at Madrasah Diniyah Miftahul Ulum Kesugihan Pulung Ponorogo. The method used in this service is the ABCD method which consists of inculturation, discovery. design, define, and reflection activities. Data collection through interviews, observation, and documentation. Based on the results of the study, it shows that the role of advocacy provides motivation for courage in defending and defending oneself so that it helps children to be more diligent in entering Madrasah Diniyah MIftahul Ulum, Kesugihan Village, Pulung District, Ponorogo Regency from the lack of defense and defense of children which causes children to be lazy to enter Madrasah Diniyah even to the point of dropped out and did not continue at the Madrasah Diniyah.